Role Of Digital Competence, Digital Culture, Individual Experience, In Increasing Job Satisfaction And Employee Performance At Bumn Banks In Palopo City - Wulandari, Fitri Amalia; Hamid, Ramhad Sholling; Ikbal, Muhammad (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the effect of digital competence, digital culture, and individual experience on job satisfaction and employee performance at the Palopo City BUMN Bank. Methodology: A quantitative approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze the data. Results: The findings indicate that digital competence has a significant effect on employee performance but does not significantly affect job satisfaction. Digital culture, however, has a significant positive effect on both job satisfaction and employee performance. Additionally, individual experience has a significant positive effect on both job satisfaction and employee performance. Findings: The study reveals that digital culture and individual experience are key factors that enhance both job satisfaction and employee performance, while digital competence primarily influences performance. Novelty: The novelty of this research lies in the integration of digital competence, culture, and individual experience in the banking sector, an area that has not received much attention in previous studies. Originality: This study is original in its focus on the banking sector and its contribution to understanding the role of digital factors in employee performance and job satisfaction. Conclusions: The study suggests developing digital competency training programs and fostering an inclusive digital culture to improve organizational performance. Type of Paper: Research paper.